META-ANALYSIS OF THE EFFECT SIZES OF DIGITAL LEARNING MEDIA ON STUDENT MOTIVATION - Mubarokah, Nadia; Fairuz, Tariza; Pardosi, Sri Masnita (Jurnal Pelita Pendidikan, 2025)
The utilization of digital learning media in science education has experienced significant growth in line with rapid technological advancements. This study aims to systematically examine the effects of various digital learning media on students’ learning motivation in science education through a meta-analytic approach. Data were analyzed from 32 relevant empirical studies published between 2017 and 2021 using Cohen’s d effect size test. The meta-analysis results indicate that video-based learning media exert the greatest influence on student motivation (d = 4.27), categorized as a very large effect size. Audio-visual media show a large effect (d = 1.22), while ICT-based media and digital games exhibit medium (d = 0.50) and small (d = 0.09) effect sizes, respectively. These findings show that the effectiveness of digital learning media in enhancing students’ motivation varies depending on the characteristics of the media used. This study is expected to provide valuable insights for educators and curriculum developers in selecting the most effective digital media to foster learning motivation in science education.